1990
DOI: 10.1590/s0074-02761990000200005
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi: experimental Chagas' disease in Rhesus monkeys. II. Ultraestructural and cytochemical studies of peroxidase and acid phosphatase activities

Abstract: Ultrastructural and cytochemical studies of peroxidase and acid phosphatase were performed in skin, lymph node and heart muscle tissue of rhesus monkeys with experimental Chagas' disease. At the site of inoculation there was a proliferative reaction with the presence of immature macrophages revealed by peroxidase technique. At the lymph node a diffuse inflammatory exudate with mononuclear cells, fibroblasts and immature activated macrophages reproduces the human pattern of acute Chagas' disease inflammatory le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…16,[51][52][53] Rhesus monkeys acutely infected with the Colombian strain also showed aggressive cardiomyopathy. 13,14 In addition, the histopathologic analysis of the chronically infected monkeys that were killed (monkeys 42 and 68) confirms the presence of mild myocarditis in absence of significant ECG abnormalities (Carvalho CME and others, unpublished data). Interestingly, we have shown that rhesus monkeys chronically infected with the Colombian strain developed electrocardiographic alterations similar to those observed in chronic chagasic patients.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…16,[51][52][53] Rhesus monkeys acutely infected with the Colombian strain also showed aggressive cardiomyopathy. 13,14 In addition, the histopathologic analysis of the chronically infected monkeys that were killed (monkeys 42 and 68) confirms the presence of mild myocarditis in absence of significant ECG abnormalities (Carvalho CME and others, unpublished data). Interestingly, we have shown that rhesus monkeys chronically infected with the Colombian strain developed electrocardiographic alterations similar to those observed in chronic chagasic patients.…”
Section: Discussionmentioning
confidence: 56%
“…A strong inflammatory reaction with lymphocytic infiltrate and eosinophils associated with ruptured cells was present. 13,14 Considering that approximately one-third of T. cruziinfected humans develop severe chronic disease with irreversible damage to the heart and/or gastrointestinal tract with dilation and disorders of nerve conduction, it is crucial to understand the mechanisms leading to these organ-specific pathologies. 15 Because these alterations are observed 10-20 years after the acute phase, we have examined long-lasting (15-19 years) T. cruzi experimental infection in seven male rhesus monkeys that were initially evaluating for the clinical, parasitologic, serologic, and hematologic aspects of the chronic infection.…”
Section: Introductionmentioning
confidence: 99%
“…Non-human primates have also been explored as models for Chagas disease (Bonecini-Almeida Mda et al, 1990; de Almeida et al, 1992; de Meirelles Mde et al, 1990; Milei et al, 1982). Early studies revealed that ECG changes in infected monkeys were correlated with specific anatomic lesions (Milei et al, 1982).…”
Section: 2 Larger Animal Modelsmentioning
confidence: 99%
“…Interestingly, similar arguments have recently appeared in the literature questioning the relevance of the mouse model of cerebral malaria to human cerebral malaria (Taylor-Robinson, 2010). Thus, several studies have employed T. cruzi -infected larger animals such as rabbits, rats, guinea pigs, dogs and subhuman primates (Barbabosa-Pliego et al, 2009; Bonecini-Almeida Mda et al, 1990; Chandrasekar et al, 1998; Chen et al, 1996; Cruz-Chan et al, 2009; da Silva et al, 1996; de Almeida et al, 1992; de Meirelles Mde et al, 1990; Figueiredo et al, 1986; Guedes et al, 2002, 2009; Junqueira Junior et al, 1992; Labrador-Hernandez et al, 2008; Milei et al, 1982; Morris et al, 1991; Perez et al, 2009; Ramirez and Brener, 1987; Teixeira et al, 1983; Zabalgoitia et al, 2004). …”
Section: 1 Introductionmentioning
confidence: 99%
“…As well as smaller mammals such as rabbits and rats 36,37 , larger animal models including dogs and non-human primates [38][39][40][41][42][43][44][45][46][47][48][49][50] are also used for experimental studies, mainly in Chagas disease, due to these mammals' capacity to host parasites. Dogs and non-human primates (baboons, macaques, and capuchin monkeys) have been important experimental models to study the pathogenesis of Chagas disease, mainly in regard to the immunopathogenic mechanisms involved in the chronic phase of T. cruzi infection 38,[42][43][44][45][46][47][48][49][50] . Electrocardiography alterations 39,40,47,49 have been reported in studies of dogs and nonhuman primates infected with several T. cruzi strains as well in studies using BZN chemotherapy in dogs who received the same regimen as humans (7mg/kg), corroborating with the outcomes of other clinical trials 42 .…”
Section: Introductionmentioning
confidence: 99%